Penilaian Kondisi Perkerasan Jalan Menggunakan Metode Bina Marga dan PCI untuk Menentukan Prioritas Penanganan Kerusakan - David Bangguna; Yulisnawati Lawodi; Elce Bansambua; Henny Abulebu; Ebelhart Pandoyu (Institut Teknologi Garut, 2026)
The objective of this study is to analyze road damage using the Bina Marga and PCI (Pavement Condition Index) methods. Both empirical methods are applied because they are commonly used to assess road damage in Indonesia. Road damage analysis using the Bina Marga method is carried out through several stages, including determining road type and classification, classifying the type and severity of damage, evaluating road damage, and recommending appropriate maintenance actions. The PCI method involves determining the Total Deduct Value (TDV), calculating the corrected deduct value, determining the PCI value, and recommending the type of road repair. The results of the Bina Marga method recommend routine maintenance, while the PCI method suggests structural rehabilitation. Considering the existing road damage conditions, routine maintenance is selected as the appropriate treatment. In the following year, if monitoring and evaluation show that damage still occurs at the repaired location, road improvement in the form of overlay is recommended.